2011
DOI: 10.1063/1.3552917
|View full text |Cite
|
Sign up to set email alerts
|

Photopatterning the mechanical properties of polydimethylsiloxane films

Abstract: Indentation of a square elastomeric thin film by a flat-ended cylindrical punch in the presence of long-range intersurface forces Silicone rubber films with graded and localized mechanical properties are prepared using two-part polydimethylsiloxane (PDMS) elastomer, photoinhibitor compounds and conventional photolithography. First the un-cross-linked PDMS is mixed with benzophenone. The resulting positive photosensitive material is then exposed through a mask to UV light from a conventional mask aligner. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
3
50
0
Order By: Relevance
“…Although elegant photolithographic approaches have been successful in locally increasing the elastic modulus of polydimethylsiloxane elastomers within the MPa range by a factor of 5 (refs 25,38), the 100-fold reduction in the local-to-global strain ratio enabled by the graded architecture outperforms previous attempts to obtain locally stiff islands that protect brittle inorganic layers from failure in stretchable electronics [25][26][27][28][29] . As the step at the patch edges might be undesired in flexible electronics, other geometries can be readily obtained using other approaches to assemble the PU compositions with different level of reinforcement, including hot-pressing, tape-casting, screenprinting and 3D rapid prototyping techniques.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although elegant photolithographic approaches have been successful in locally increasing the elastic modulus of polydimethylsiloxane elastomers within the MPa range by a factor of 5 (refs 25,38), the 100-fold reduction in the local-to-global strain ratio enabled by the graded architecture outperforms previous attempts to obtain locally stiff islands that protect brittle inorganic layers from failure in stretchable electronics [25][26][27][28][29] . As the step at the patch edges might be undesired in flexible electronics, other geometries can be readily obtained using other approaches to assemble the PU compositions with different level of reinforcement, including hot-pressing, tape-casting, screenprinting and 3D rapid prototyping techniques.…”
Section: Discussionmentioning
confidence: 94%
“…Obtaining such level of 3D control in artificial heterogeneous composites would allow us to not only extend the lifetime of existing functional devices prone to interfacial failure but also to develop new materials for mechanically challenging demands. These include for example dental restorations for prosthetic dentistry that more closely resemble the mechanical properties of natural tooth 23 , elastomeric substrates for flexible electronics that are bendable and stretchable but yet locally stiff [24][25][26][27][28][29] and synthetic bioscaffolds for the replacement of intervertebral discs 30 and for the regeneration of graded tendon/ligament-to-bone insertions [31][32][33] . In addition to addressing such mechanical challenges, the deliberate local reinforcement of weak regions achievable with such heterogeneous composites also represents an economical and environmental-friendly approach to attain the required mechanical performance while minimizing the use of limited and costly resources.…”
mentioning
confidence: 99%
“…Excessive strain is distributed across soft/hard interfaces by grading mechanical strength. 72 The edges of device islands are feathered out, 68 the elastomer below the island is hardened chemically 33 or by insertion of rigid plates, 33 or the interconnect is made to vary from wide and stiff on the island to narrow and compliant on the elastomer (see the Vanfl eteren et al article).…”
Section: Devices and Circuitsmentioning
confidence: 99%
“…Thus, by using standard UV-photolithography, multilayer structures, and multilevel microfluidic chips based on PDMS can be fabricated. Further, it has been shown that the same technological approach can be used to realize silicone rubber films with graded and locally modified mechanical properties [17]. PDMS bilayer films with embedded spontaneous curvatures have been realized by preparing PDMS/(PDMS ?…”
Section: Pdms-based Actuatorsmentioning
confidence: 99%